Targeted therapy for hepatocellular carcinoma: Challenges and opportunities - Chen, Shuzhen; Cao, Qiqi; Wen, Wen; Wang, Hongyang (Cancer letters, 2019)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide, which ranks as the sixth of cancer-related death. Despite the emergence of targeted therapy, advanced-stage HCC remains largely incurable due to low response rate and therapeutic resistance. In this review, we mainly focused on the current progression of multi-kinase inhibitors and immunotherapies in the treatment of HCC. We highlight the mechanism underlying the ineffectiveness of these targeted therapies, including oncogenic alterations in driver genes and downstream pathways, high heterogeneity of HCC, and the mutual interaction of tumor microenvironment that promotes therapeutic resistance. We also discussed how these previous studies suggested for future therapeutic strategies. Besides, the complexity of HCC heterogeneity and cancer revolution need to be recognized in personalized therapy. Establishment of a drug screening system and identification of biomarkers of response is also in urgent need to overcome drug resistance. Meanwhile, a combination of targeted therapies could also be explored as a promising strategy in the future. •Despite the emergence of targeted therapy, advanced-stage HCC remains largely incurable due to therapeutic resistance.•Multiple factors contribute to drug resistance of HCC patients against MKIs.•Further studies are expected to identify biomarkers for response and promote efficacy of immunotherapy.•Insight into heterogeneity of HCC and combined therapy could be the next step forward the future of precision medicine.